"Cubism" on the Nanoscale: From Squaric Acid to Porous Carbon Cubes. Issue 21 (7th April 2016) - Mani, Christian Mbaya; Berthold, Thomas; Fechler, Nina
Abstract : 3D cube‐shaped composites and carbon microparticles with hierarchically porous structure are prepared by a facile template‐free synthesis route. Via the coordination of zinc acetate dihydrate and squaric acid, porous 3D cubic crystalline particles of zinc squarate can be obtained. These are easily transformed into the respective zinc oxide carbon composites under preservation of the macromorphology by heat treatment. Washing of the composite materials results in hierarchically porous carbons with high surface areas (1295 m 2 g –1 ) and large pore volumes (1.5 cm 3 g −1 ) under full retention of the cube‐like architecture of the initial crystals. The materials are shown to be promising electrode materials for supercapacitor applications with a specific capacitance of 133 F g −1 in H2 SO4 at a scan rate of 5 mV s −1, while 67% of this specific capacitance is retained, when increasing the scan rate to 200 mV s −1 . Abstract : Porous carbon nanocubes are prepared via a facile one‐pot approach using the complexation of squaric acid and zinc ions. This method can also be extended to other geometries that allow for rational carbon structuring, and thus targeted design for applications such as energy storage devices.